PENERAPAN MODEL COOPERATIVE TIPE MAKE A MATCH PADA MATERI ORGAN GERAK HEWAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V MIN 17 PIDIE - Junaidah (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2021)
The purpose of this study was to determine the application of the Make a Match Type Cooperative model in improving student learning outcomes for class V MIN 17 Pidie. Classroom action research consists of three cycles with the steps of planning, acting, observing, and reflecting. The research subjects were students of class V with a total of 34 people consisting of 22 women and 12 men. The results of the study obtained student scores with an average value and the percentage of completeness according to the cycle, namely in the first cycle, 65 and 41.18% were obtained. In the second cycle obtained 75.29 and 70.58%. And in the third cycle obtained 92.35 and 100%.